Voice Quality in British English. Its Nature, Functions and Applications - Stephan Wilhelm (Anglophonia)
This paper deals with the functions of voice quality. It also suggests that a number of practical applications can be derived from the study of these functions.Like e.g. Laver (1968; 1980), Sharpe (1970) or Mackenzie-Beck (2005), we take voice quality to refer to the quality of the human voice in the production of language that results from both phonatory (laryngeal) and articulatory (supralaryngeal) adjustments. We also think that voice quality should be included among suprasegmental elements insofar as phonatory and articulatory settings, when conceived of as components of voice quality, fulfil a function that is superposed to that of the phonatory and articulatory components of any acoustic realisation of the English phonemes.We first survey the main types of voice quality. We then show that, in British English, some of these voice types can fulfil not only linguistic or paralinguistic functions, but also, most importantly, an extralinguistic function. On a sociolinguistic level, we give evidence that, in some cases at least, voice quality constitutes a reliable marker of geographical or social origins. We suggest that, like segmental elements or intonation features, the use of voice quality settings can spread through processes of social or geographical diffusion. Lastly, we point out that the study of voice quality may prove useful in a wide variety of domains such as forensic linguistics, voice recognition, speech synthesis and crucially EFL teaching.